Low cost animal drawn implements for Vertisol management and strategies for land use intensification - Astatke, A.; Jabbar, M.A. (American Association of Engineering Societie, 2000)
The main aim of land preparation is to modify and manipulate the land features so as to create favorable environment for seed establishment and crop growth. The research and Development in this field must take into account the traditional practices used by the farming community. This case study gives a brief description of farmers' management of Vertisols and soils with 'Vertic' properties and the Development of the low cost broad bed maker (BBM) for facilitating surface drainage. Other attachments like planters and cultivators to the BBM for minimum tillage system which are going to be tested on-farm are also discussed. Topics of discussion include traditional management of Vertisols and land use types; importance of Vertisols in the East African highland; and land use intensification opportunities. The paper also describes and looks into the traditional implement 'Maresha' the broad bed maker and its evolution; and the additional attachments to the BBM for improving tillage efficiency and resource conservation.